1983
DOI: 10.1002/bit.260250221
|View full text |Cite
|
Sign up to set email alerts
|

Growth and anthocyanin accumulation rates of carrot suspension cultures grown with excess nutrients after semicontinuous culture with different limiting nutrients at several dilution rates, pHs, and temperatures

Abstract: When carrot cell cultures, after growth in semicontinuous culture, were transferred to media containing excess nutrients, they grew at different rates. The growth rates were generally higher after semicontinuous culture at higher dilution rates. There appears to be a limit on dilution rate above which growth rate does not increase. These changes were also displayed by clones from the parental culture. The possibility that these changes in growth rate reflect a need for the cultures to adapt to their new condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Tal & Goldberg obtained good cell growth with little steroid synthesis in continuous fermentations of Dioscorea deltoidea [54]. Dougall and coworkers, in culturing Daucus carotaon a continuous basis demonstrated that factors which improve biomass productivity either do not affect product formation or actually inhibit it [104,105]. This naturally leads to a process whereby biomass and product synthesis are uncoupled.…”
Section: Process Systemsmentioning
confidence: 99%
“…Tal & Goldberg obtained good cell growth with little steroid synthesis in continuous fermentations of Dioscorea deltoidea [54]. Dougall and coworkers, in culturing Daucus carotaon a continuous basis demonstrated that factors which improve biomass productivity either do not affect product formation or actually inhibit it [104,105]. This naturally leads to a process whereby biomass and product synthesis are uncoupled.…”
Section: Process Systemsmentioning
confidence: 99%
“…Callus and cell suspension culture systems have been a good platform to understand the engineering of anthocyanin biosynthesis regulated by 2,4-D for a few decades (Ball 1967; Stickland and Sunderland 1972; Wellmann et al 1976; Dougall et al 1980; Al Qurraan et al 2012; Asano and Otobe 2011). Example models of callus and cell suspension cultures include carrot (Dougall et al 1980; Dougall et al 1983; Rose et al 1996; Hirner and Seitz 2000; Narayan et al 2005; Ozeki et al 2000), grape (Bao Do and Cormier 1991; Do and Cormier 1991a; Do and Cormier 1991b; Cormier et al 1992; Yousef et al 2004), and Catharanthus roseus (Hall and Yeoman 1986b, a). Based on those previous reports, the regulation of 2, 4-D can be summarized to two types.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of anthocyanin accumulation (Dougall et al 1983) and degradation (Dougall & Vogelien 1987) were examined in extreme clones, and no difference was detected that would account for the difference in anthocyanin levels observed. The enzyme 4-coumaryl CoA ligase was examined in high-and low-accumulating subclones to investigate the possible role of isozymes of this enzyme in directing 4-coumaryl CoA to lignin biosynthesis, flavonoid biosynthesis and other pathways.…”
Section: Introductionmentioning
confidence: 99%